Optimizing Branding and Digital Marketing as a Strategy to Increase the Competitiveness of MSMEs in Banban Village - Nailatur Rohmah; Mutfaidah, Mutfaidah; Fatimatus Syafira; Uzlifatul Masruroh; Fera Mei Khotuzzahroh; Kholifatun Nisa; Fadllan, Fadllan (Penerbit Hellow Pustaka, 2025)
Optimization of branding and digital marketing is a crucial strategy for enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in today’s digital era. This study aims to examine the implementation of rebranding programs and the digitalization of MSME marketing in Banban Village, Pakong District, Pamekasan Regency, conducted by students from the Community Service Program (KKN) of the State Islamic University of Madura as part of efforts to develop local products. The research employed a qualitative descriptive approach, with data collected through direct observation, in-depth interviews, and documentation of program activities. Findings indicate that the implementation of representative product logo creation, installation of location points on Google Maps, and the use of visual promotional media such as banners significantly contributed to improving brand image and increasing MSME sales revenue. Based on these findings, it is recommended that MSME actors continuously optimize the use of digital platforms and strengthen branding as a sustainable strategic effort to improve market competitiveness.